Rehospitalization of a Recovered Coronavirus Disease 19 (COVID-19) Child With Positive Nucleic Acid Detection. Issue 6 (June 2020) - Wang, Haizhou; Li, Ying; Wang, Fan; Du, Hui; Lu, Xiaoxia
Abstract : Since December 2019, novel coronavirus-infected pneumonia (coronavirus disease 19) occurred in Wuhan and rapidly spread throughout China and beyond. During this period, increasing of reports found that several recovered patients from different hospitals showed positive results of nucleic acid test again soon after discharge. However, little attention has been paid to recovered children. Herein, we reported a case of 8-year-old recovered child, who was rehospitalized again because of unexplained fever.